A Systematic Review of Extended Reality (XR) Technologies in Agriculture and Related Sectors (2022–2024) - Maryam Bigonah; Fatemeh Jamshidi; Aparana Pant; Sanjaya Poudel; Sasikiran Reddy Nallapareddy; Atefeh Charmchian Langroudi; Daniela Marghitu (IEEE Access)
The agricultural sector confronts critical challenges such as climate change, overpopulation, and resource shortages, necessitating urgent innovative solutions. In this context, Extended Reality (XR) technologies have emerged as a transformative technology, offering groundbreaking approaches to modern farming practices. This study conducts a thorough literature review to explore the integration of XR technologies in agriculture, livestock farming, and aquaculture. By categorizing studies based on focus areas, application types, and human-machine interaction dimensions, it identifies emerging trends, highlights critical gaps, and proposes future direction for advancing these fields. The analysis revealed a significant increase in XR technology adoption over the past two years, highlighting its potential within the sector. The findings suggest that XR technologies can enhance productivity, improve training methods, and facilitate remote collaboration in agricultural settings. However, future research should focus on addressing health, privacy, and security concerns to enhance seamless and immersive XR experiences, thereby maximizing the potential benefits of XR technology in the primary sector. Therefore, these technologies will transform the agriculture industry, fostering a resilient and sustainable food system to meet the demands of a growing global population.